Smart tourism: how can we count on digital in the recovery of post-covid tourism in Portugal - Lopes, Isabel Maria (2022)
The number of tourists who visited Portugal in 2019 reached historic highs, a trend that was eventually interrupted by the emergence of the pandemic caused by the SARS-CoV-2 virus. Several experts point out that tourism was one of the first sectors to suffer the impacts of the pandemic and one of the hardest to be hit. Tourism recovery is desirable and what needs to be clarified with this study is how the digital transition so present, for example, in the Recovery and Resilience Plan (PRR) can help to rescue this upward trend of visitors/tourists. The present research work intends to emphasize how digital can be decisive in the resumption of tourism in Portugal, taking into account the measures announced for this sector. The results are discussed in the light of the literature and future work is identified with a view to enhancing tourism, smart tourism and smart destinations.